Data-Driven Process Discovery and Analysis First International Symposium, SIMPDA 2011, Campione D'Italia, Italy, June 29 - July 1, 2011, Revised Selected Papers - Aberer, Karl; Damiani, Ernesto; Dillon, Tharam (Lecture Notes in Business Information Processing,, 2012)
This book constitutes the thoroughly refereed proceedings of the First International Symposium on Data-Driven Process Discovery and Analysis held in Campione d'Italia, Italy, in June/July 2011.The 11 revised full papers were carefully selected from 31 submissions. In addition to the thorough review process, the lively discussions at the event itself also helped the authors to improve their papers and to foster interesting extensions. The selected papers cover a wide range of topics spanning theoretical issues related to process representation to practical experience in process discovery and analysis.